The Influence of the Utilization of QRIS and Digital Marketing Strategies on Purchase Decisions through Consumer Satisfaction in MSMEs at the State University of Jakarta - Yeni Hesti Verawati Manurung; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2025)
This study aims to analyze the effect of QRIS utilization and digital marketing strategies on purchase decisions, mediated by consumer satisfaction, among students of the State University of Jakarta who have made purchases at MSMEs. This research employs a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS, involving 85 student respondents. The results indicate that QRIS utilization has a positive and significant effect on consumer satisfaction and purchase decisions (H1 and H3), while digital marketing strategies also positively influence consumer satisfaction and purchase decisions (H2 and H4). Furthermore, consumer satisfaction is proven to have a positive and significant effect on purchase decisions (H5) and mediates the relationship between QRIS utilization and purchase decisions, as well as between digital marketing strategies and purchase decisions.